A flight-based metric for evaluating NFL punters - Pasteur, R. D.; Howerton, E.; Pozderac, P.; Young, S.; Moore, J. (Journal of Sports Analytics, 2018)
Common evaluation metrics for NFL punters are outdated, failing to account for field position and touchbacks. Using detailed information on each punt of the 2013 season, a nonlinear model is developed, using these factors alongside hang time, coverage quality, and environmental conditions. This leads to punter evaluation metrics using expected points added (EPA), both in total and per punt. The persistence of punting skill is explored, and the relationships between performance and salary are discussed.